Analisis Faktor-Faktor Yang Mempengaruhi Pengguna Untuk Mengadopsi Teknologi Komputasi Awan (Cloud Computing) Menggunakan Pendekatan Technology Acceptance Model - MUNTHE, Abraham Septa Creado ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was conducted to analyze the factors that influence the users in adopting or using cloud computing services. These factors were taken from the dimensions of Technology Acceptance Model (TAM) in the form of perceived ease of use, perceived usefulness, and attitude toward using with two external variable: personal innovativeness and quality of internet connection. Respondent sample was taken using purposive sampling technique. Data analysis was performed with Structural Equation Model (SEM). The applications that are used to analyze the data is AMOS 19. The result of this research showed that (1) Attitude toward using cloud computing positively influenced by perceived ease of use and perceived usefulness, (2) perceived ease of use positively influenced by personal innovativeness, (3) Intention to use cloud computing positively influenced by personal innovativeness and attitude toward using, and (4) quality of internet connection has no effect on use intention of cloud computing.